Writing essentials and checklist of integrated traditional Chinese and western medicine nursing ward round case report (中西医结合护理查房案写作要点和核对清单) - LI Ye (李野); GUO Hong (郭红); E Haiyan (鄂海燕); YE Zhenhua (叶振华); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
As an important link in daily nursing practice, nursing ward round can reflect the working ability, nursing quality and professional quality of nursing staff. By reviewing the related medical report and guideat home and abroad, this paper try to summarize writing essentials and develop a checklist of integrated traditional Chinese and western medicine nursing ward-round case report. Focusing on the purpose, organization, implementation and evaluation of nursing ward round, the checklist was designed to help nursing workers write high quality nursing ward round case report, and promote the standardization and application of integrated traditional Chinese and western medicine nursing case report. (护理查房作为护理人员日常工作中的重要环节, 能够体现护理人员的工作能力、护理质量以及业务素质。本文参考国内外相关病案报告指南, 尝试编制"中西医结合护理查房案写作要点和核对清单", 重点对查房目标、查房组织、查房实施、查房评价四方面结构模块化, 为国内护理工作者撰写高质量护理查房案例报告提供借鉴和参考, 推动中西医结合护理案例报告规范的制定和推广应用。)